45.3: Invited paper: Problem Solving about Image Sticking through Order Parameter. (28th November 2018) - Li, Zhengqiang; Xu, Kai; Su, Mark
Abstract : Order Parameter (OP) controls almost every physical properties of liquid crystal including Tni, △n and △ε…. Moreover, we found that order parameter of LC material is strongly related to image sticking performance. In another words, the image sticking performance can be predicted and optimized by using the index of order parameter. Hereinafter, further on in this document about the fundamental mechanism in between order parameter and image sticking performance and also how to control order parameter will be introduced. It should be pointed out that order parameter only representing the capability of LC material itself against image sticking issue, and ignore the influence factors from material collocation such as LC/PI.